PEMERIKSAAN GLUKOSA, KOLESTEROL DAN ASAM URAT UNTUK MENINGKATKAN KESEHATAN MASYARAKAT DI KAMPUNG DISTRIK DEPAPRE KABUPATEN JAYAPURA TAHUN 2021 - Asrianto ,; Indra Taufik Sahli; Asrori ,; Rina Purwati; Dwi Setiani (ABDIKEMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Diabetes Mellitus is a chronic metabolic disorder that occurs due to various causes, characterized by blood glucose concentrations exceeding normal, and impaired carbohydrate, fat, and protein metabolism caused by abnormalities in insulin hormone secretion or insulin action abnormalities. Efforts to reduce or detect the distribution of cases of diabetes mellitus require early screening. The screening is done by checking the respondent's blood sugar, cholesterol, and uric acid. Based on the results of the health examination, which included blood sugar, it showed that from 36 respondents, 6 (16.66%) women had high blood sugar; this should be suspected due to age, consumption patterns, and lack of physical activity. Cholesterol examination results showed that 5 (13.88%) men and 4 (11.11%) women had abnormal blood cholesterol levels; this should be suspected to be influenced by the consumption pattern of foods containing high cholesterol. The results of the uric acid examination showed that 3 (8.33%) men and 4 (11.11%) women had abnormal uric acid levels; this is thought to be due to the habit of people who like to consume see food foods that have high purine content. This community service is essential to increase public awareness to check themselves periodically for their health.